Improving Kindergarten Children's Fine Motor Development through Montessori Practical Life Activities Integrated with Project-Based Learning - Norhasan Norhasan; Muhammad Dani Wahyudi (Borneo Research and Education Center, 2025)
Fine motor competence is a foundational component of early childhood development because it supports children's readiness to participate in drawing, writing, manipulating learning materials, self-care routines, and early mathematical activities. This classroom action research aimed to describe teacher activity, children's learning activity, and children's fine motor development after the implementation of Montessori Practical Life activities integrated with Project-Based Learning (PjBL). The study was conducted in a kindergarten class in Banjarmasin, Indonesia, involving 14 Group A children, consisting of eight boys and six girls. The action was implemented in two cycles across four meetings. Data were collected through observation sheets, interviews, documentation, and a fine motor development rubric, and were analyzed descriptively using percentage achievement and category interpretation. The findings indicated continuous improvement across all observed dimensions. Teacher activity increased from 50% in Meeting 1 to 96% in Meeting 4, children's learning activity increased from 14% to 93%, and classical fine motor development increased from 36% to 100%. The results suggest that combining Montessori Practical Life and PjBL can create concrete, meaningful, child-centered, and product-oriented learning experiences that stimulate hand-eye coordination, finger control, concentration, independence, collaboration, and task completion. Nevertheless, the findings should be interpreted cautiously because the study involved one small class and did not use a comparison group. The study contributes practical classroom evidence on how everyday-life Montessori activities can be strengthened through project-based learning to support fine motor development in early childhood education.